Investigating the experiences in a school-based occupational therapy program to inform community-based paediatric occupational therapy practice - Rens, L.; Joosten, Annette (Wiley-Blackwell Publishing Asia, 2013)
Background/aimA collaborative approach with teachers is required when providing community-based occupational therapy to educationally at risk children. Collaborators share common goals and interact and support each other but challenges arise in providing collaborative occupational therapy in settings outside the school environment. The aim of this study was to capture experiences of teachers and occupational therapists working within a school-based occupational therapy program to determine if their experiences could inform collaborative practice.MethodIn this pilot study, participant responses to questionnaires (n = 32) about their experiences formed the basis for focus groups and individual interviews. Two focus group were conducted, one with teachers (n = 11) and one with occupational therapy participants (n = 6). Individual interviews were conducted with the supervising occupational therapist, school principal and two leading teachers. Descriptive statistics were used to analyse the data from closed questions, and thematic analysis using a constant comparison approach was used to analyse open ended questions, focus groups and interviews.ResultsThree main themes emerged: (i) the need for occupational therapists to spend time in the school, to explain their role, build relationships, understand classroom routines and the teacher role; (ii) occupational therapists need to not see themselves as the expert but develop equal partnerships to set collaborative goals and (iii) occupational therapists advocating for all parties to be informed throughout the occupational therapy process.ConclusionThe pilot study findings identified teacher and therapist experiences within the school setting that could inform improved collaborative practice with teachers and community-based occupational therapists and these findings warrant further investigation.